PROGNOSTIC MARKERS FOR THROMBOTIC EVENTS IN PATIENTS WITH GASTRIC OR COLORECTAL ADENOCARCINOMAS - Emilly de Assis MACHADO; Marcelo Gerardin Poirot LAND; Alberto SCHANAIDER (ABCD: Arquivos Brasileiros de Cirurgia Digestiva)
ABSTRACT BACKGROUND: The relationship between thrombosis and cancer is based on evidence that cancer promotes prothrombotic changes in the host hemostatic system. The activation of blood coagulation is closely linked to tumor growth and dissemination. AIMS: To evaluate whether quantifications of plasma circulation tumor deoxyribonucleic acid (DNA) and thrombin-antithrombin complex could act as predictors for thrombotic events and death in patients with gastric or colorectal adenocarcinomas, while also evaluating the Karnofsky Performance Status. METHODS: Eighty-two patients were included in the study and divided into three groups: controls (n=20), gastric adenocarcinomas (n=21), and colorectal adenocarcinomas (n=41). In order to calculate the Karnofsky index, information was collected to measure the patient’s ability to perform common daily tasks. The following serum measurements were conducted: complete blood count, platelet count, extracellular deoxyribonucleic acid, and thrombin-antithrombin complex. RESULTS: Ten patients (16%) experienced thrombosis during treatment. Patients with thrombin-antithrombin complex levels greater than 0.53 had a five-times higher risk of thrombosis. Lower Karnofsky Performance Status was also a risk factor for the event in this population. Neither thrombin-antithrombin complex nor plasma circulation tumor DNA were predictors of death after multivariate adjustment. Thus, Karnofsky index signaled a better overall survival prognosis for colorectal and gastric adenocarcinoma patients. CONCLUSIONS: Thrombin-antithrombin complex acts as a marker for thrombosis in patients with colorectal and gastric adenocarcinomas. We recommend prophylactic anticoagulation when the Karnofsky value is low and/or the thrombin-antithrombin complex concentration is greater than 0.53 ng/ml.